KARAKTERISTIK PEMILIH DI KABUPATEN SIDENRENG RAPPANG PADA PEMILIHAN LEGISLATIF DALAM PERSPEKTIF TEORI PILIHAN PUBLIK - Suhardi Junaidi; Muhammad Rais Rahmat; Adam Latif (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of this study is to determine the characteristics of voters in Sidenreng Rappang regency in the election of the slative legislature. The sample of data sources in this study amounted to 8 people based on purposive samplinf technique. This type of research is descriptive qualitative. Data collection techniques used in this study were observation and interviews. The data analysis technique used in this study is qualitative analysis used by researchs, namely data collection, data reducation, data presentation, and the last step is drawing conclusions.The result of this study are the characteristics of voters in Sidenreng Rappang regency in the legislative election based on the results of interviews from several respondents so that the researchers found the results that the people of Sidenreng Rappang regency, especially in the two electoral districst have several characteristics, including traditional voters, rational voters, and skeptical voters.